INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM MENCEGAH PERILAKU BULLYING (Studi Kasus di MTs Nurul Ulum Malang) - Aliy Ahmad; Rosichin Mansur; Ach Faisol (VICRATINA, 2020)
Internalization is a process of entering values or entering ideal attitudes that were previously considered to be outside, so that they are corporated in thoughts, skills and attitudes of person's life outlook. Value is a preference that is reflected in a person's behavior, so that he does or does not to do something. In this case, value is a concept, attitude and belief in something that is considered important. Islamic religious education as a view of life and attitude will have certain implications, both positive and negative, since religious education has the potential to lead to tolerance or intolerance, potential to realize integration (unity and integrity) or disintegration (division) in people's lives. Bullying is a situation where an abuse of power is carried out by a person or group. A power person or group here not only means strong in physical size, but also can be mentally strong.